Design of an Electro-Absorption Modulator Based on Graphene-on-Silicon Slot Waveguide - Lanting Ji; Daming Zhang; Yan Xu; Yang Gao; Chi Wu; Xibin Wang; Zhiyong Li; Xiaoqiang Sun (IEEE Photonics Journal, 2019)
Compact high-performance electro-optic (EO) modulators are key elements for optical communications. An electro-absorption modulator is theoretically designed. Due to the introduction of graphene film over the silicon slot waveguide, the modulation efficiency is strongly improved. The effect of waveguide dimensions, dielectric insulator thickness, and carrier mobility on performances of the proposed EO modulator have been comprehensively investigated. For the 120-μm-long graphene-on-silicon waveguide modulator, the extinction ratio 28 dB and insertion loss 1.28 dB can be obtained at 1550 nm when drive voltage is 1.91 and 0.59 V, respectively. The 3 dB bandwidth of 117 GHz can be obtained at a small power consumption of 212 fJ/bit. The proposed modulator possesses a high figure-of-merit of 20.5. Its benefits of small size, power saving, and process compatible promises possible applications in on-chip signal processing.